2019
DOI: 10.18502/ijpho.v9i3.1166
|View full text |Cite
|
Sign up to set email alerts
|

Seizure following acute hemolysis caused by Glucose-6-phosphate dehydrogenase Deficiency

Abstract: Background: Storage of platelet concentrates (PCs) at room temperature (20-24°C) limits its storage time to 5 Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common inherited enzyme deficiency of the human red blood cells . Most of G6PD deficient individuals are asymptomatic, but acute hemolytic anemia may be presented with nausea, vomiting, abdominal pain, headache, jaundice, pallor, discoloration of the urine, chills, and fever. Seizure is reported as a rare symptom, as well. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Of them, 6 studies were included in the meta-analysis. [25,[33][34][35][36][37] The references of the included studies were manually searched, and no further articles were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram of the study selection process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of them, 6 studies were included in the meta-analysis. [25,[33][34][35][36][37] The references of the included studies were manually searched, and no further articles were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram of the study selection process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…[38] In our review, most of the included studies in the analysis investigated the efficacy of VitE on patients with chronic hemolysis [25,33,34,36,37] and only 1 study investigated the efficacy of acute hemolysis. [35]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations